Providing of a highly specialized medical care for servicemen of the Armed Forces of Ukraine by roentgen-endovascular interventional methods - K. V. Humeniuk; I. I. Hangal; K. K. Karpenko (Zaporožskij Medicinskij Žurnal)
Aim: to provide high-quality and full-fledged minimally invasive highly specialized medical care by X-ray endovascular methods, according to modern world standards, for the Armed Forces of Ukraine on all territories of the country and direct participants of combat operations in the context of Joint Forces Operation (JFO) in certain parts of Donetsk and Luhansk regions.